Public-Private Partnerships : Collaboration between Governments and Tech Companies on Cybersecurity in the European Union - Matusevich, Elizaveta; Rolenc, Jan Martin, 1980-; Šitera, Daniel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This Master's thesis investigates the evolving necessity of Public-Private Partnerships (PPPs) for addressing complex cyber threats across the European Union. It posits that effective cyber resilience in a digitally interdependent world requires integrating private sector capabilities beyond traditional state-centric security paradigms. The study explores the multifaceted role, characteristics, and typologies of cybersecurity PPPs within the EU, examining their efficacy in confronting transnational threats to critical infrastructure and proposing strategic policy enhancements. The thesis employs comparative case studies to analyze diverse collaborative models. This research aims to deepen the understanding of how public-private cooperation can foster a robust and adaptive security architecture for Europe's digital future.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses